Erratum: Ultrafast intermodal third harmonic generation in a liquid core step-index fiber filled with C2Cl4 (Optics Express (2020) 28:17 (25037-25047) DOI: 10.1364/OE.399771) - Schaarschmidt, Kay; Kobelke, Jens; Nolte, Stefan; Meyer, Tobias; Schmidt, Markus A. (Optics Express, 2021)
We provide a correction due to an erroneous repetition rate of one of the laser systems (90 fs pulse duration) in our previously published paper [Opt. Express 28, 25037 (2020)].
CRIS-Team Scopus Importer:2023-04-20